The return of Podolia to Poland - Stolicki, Jarosław (Balcanica Posnaniensia. Acta et studia, 2003)
In accordance with the provisions of the Treaty of Karlowitz, the Polish-Lithuanian Commonwealth regained Podolia with Kamieniec Podolski after more than 25 years of Turkish rule over the region. The aim of this article is to present the mechanisms and circumstances of the evacuation of Kamieniec by the Turkish side and the actions taken to reattach the fortress to the Polish-Lithuanian Commonwealth. The author focuses on the role of commissioners, including Hetman Stanisław Jabłonowski and Kiev Voivode Marcin Kątski, who played a key role in taking over the fortress and securing it from a military point of view. An important place is given to the analysis of the activities of local assemblies and the Sejm, especially in the context of the organisation of local administration and the staffing of the fortress. The study uses manuscript sources, including correspondence and reports from commissioners, Sejm resolutions, Sejm diaries and regional council records. The author also draws on lesser-known sources from Lviv and Kiev. The analysis shows that the process of evacuating the Ottoman troops and the takeover of Kamianets-Podilskyi by the Polish-Lithuanian side was lengthy and fraught with tension. The final handover of the fortress took place on 22 September 1699, and a day later a ceremonial Podolian regional council was held.